Circularly Polarized Reconfigurable Antenna Based on Liquid Metal Switching for Dual WiMAX Bands - Vahid Sharbati; Xiulong Bao; John J. Healy; Nan Zhang; Khatereh Nadali; Max J. Ammann (IEEE Open Journal of Antennas and Propagation)
This article introduces an innovative reconfigurable antenna (RA) designed for circular polarization on the dual WiMAX frequency bands (3.5 GHz and 5.8 GHz) utilizing liquid metal switching capabilities. The antenna achieves circular polarization reconfiguration by employing a liquid metal switch connecting the parasitic element (R2) to the feed line. Notably, the liquid metal switch offers distinct advantages, including power savings in the ON state and precise control of liquid metal movement through applied voltage. The dynamic manipulation of Eutectic Gallium-Indium (EGaIn) within microfluidic channels enables efficient displacement, resulting in a 3 dB axial ratio bandwidth of (2.5–3.7 GHz) in the OFF state and (5.45–6 GHz) in the ON state. For the first time, the concept of liquid metal switches introduces a novel capability: the ability to maintain the “ON” state without the need for a continuous voltage supply. The proposed reconfigurable antenna demonstrates notable improvements in switching performance, with observed effectiveness in RF switching.